Pendidikan Agama Islam dalam Membangun Ketahanan Keluarga di Era Digital - Ifa Datuzuhriah; Munir; Karoma (TAUJIH: Jurnal Pendidikan Islam, 2024)
Significant changes have occurred in human life in the digital era, especially in the family context. Building family resilience will help you anticipate the positive and negative impacts of digital technology. Islamic religious education has an important role in fostering family resilience in the digital era by instilling moral principles that can become a solid foundation in overcoming various obstacles. The aim of this research is to provide practical recommendations for families and religious educators in increasing family resilience through religious education that is relevant to the digital context. Qualitative research using literature study techniques is the methodology used. Information is collected from a number of sources, including relevant books, journals and articles. Based on research findings, Islamic religious education plays an important role in fostering family resilience in the digital era by instilling moral and spiritual values ​​such as love, communication and harmony. The availability of religious education tools, family knowledge of the importance of religious values, and the involvement of religious figures are factors that encourage the use of Islamic religious education in building family resilience in the digital era. The family's lack of knowledge and understanding regarding the negative impacts of digital technology, limited access to religious learning materials, and lack of assistance from other parties are examples of obstacles.